Investigating Psychometric Properties of “NEO-Five Factor Inventory” (NEO-FFI) - R. Roshan Chesly; M.R. Shaeeri; M. Atrifard; A. Nikkhah; B. Ghaem Maghami; A. Rahimierad (روانشناسی بالینی و شخصیت, 2006)
The major aim of this research was to investigate psychometric properties of “NEO-Five Factor Inventory” (NEO-FFI). To this aim, after doing preliminary stages and resolving possible problems, the exploration of this scale was conducted in two studies: in the first study, in order to assess reliability using internal consistency, 604 undergraduate students of Tehran, Amirkabir and Shahed Universities (334= female and 270= male) with average age of 21.8 (sd=2.49) were selected by available sampling method. Students completed NEO-FFI. Results of this study indicated that Neuroticism and Conscientiousness had acceptable internal consistency in all subjects (higher than 0.70). Of course, Cronbach Alfa of Extroversion and Agreeableness were higher than suggested level for group comparisons (higher than 0.5). Therefore, only openness lacked acceptable internal consistency. In the second study, in order to assess construct validity of NEO-FFI, Pearson’s product-moment correlation was calculated for five factors of NEO-FFI and 9 facets of “Symptom Checklist-90- Revised” (SCL-90-R). Results of these analyses indicated that Neuroticism with all facets of SCL-90-R, Conscientiousness with all facets of SCL-90-R with the exception of paranoid thinking (Bonferroni correction not considered) and obsessive-compulsive facets (Bonferroni correction considered), Agreeableness and Extroversion with 3 and 7 facets of SCL-90-R (Bonferroni correction considered) had significant correlation. Openness did not show any significant correlation with facets of SCL-90-R. Besides, among these factors, only the relationships of Neuroticism with facets of SCL-90-R was a significant positive correlation and the remaining factors had not significant correlation or had significant negative correlation with facets of SCL-90-R. In conclusion, results of this study with respect to literature review about investigating psychometric properties of NEO-FFI in non-English cultures suggest need to investigate factor structure of this in Iranian population.